Ultrasound-guided versus blind intraarticular injection of the foot of Egyptian buffaloes (Bubalus bubalis): A pilot study - EL-SHAFAEY, EL-SAYED; ABDELLATIF, AHMED; ELFADL, EMAN ABO; MOHAMAD, ZAKRIYA AL; HAMED, MOHAMED A (The Indian Journal of Animal Sciences, 2023)
This study was designed to compare the effectiveness of US-guided and blind IA injection techniques of buffaloes foot. Twenty adult buffalo cadaveric hind feet were randomly assigned to blind (n=10) and US-guided (n=10) injections of the fetlock, pastern, and coffin joints. Methylene blue (1%) and Iopamidol® 300 (5 ml) were used as indicative markers for IA injection. The same injection strategy was also used in vivo on 10 live sound buffaloes. The injection criteria were comparatively evaluated between the two injection techniques. The US-guided injection technique showed a significant increase in the injection parameters of the fetlock, pastern, and coffin joints in the foot of buffaloes compared with the blind technique. However, the difficulties of the injection and several trials weresignificantly higher in the blind IA injection than in the US-guided injection. The performance time was significantly shorter with the US-guided injection as compared to blind IA injection. Compared to the blind approach, US-guided injection had the highest specificity for intra-articular injection procedures at 86.66%. In conclusion, US-guided IA injection of buffaloes feet showed promising results in enhancing the quality of diagnostic and therapeutic IA injections compared to blind injections.